2019
DOI: 10.25186/cs.v14i3.1585
|View full text |Cite
|
Sign up to set email alerts
|

INITIAL STAGES OF INFECTIOUS PROCESS OF Pseudomonas syringae pv. garcae IN COFFEE LEAVES

Abstract: <p>Bacterial blight of coffee (<em>Pseudomonas</em> <em>syringae</em> pv. <em>garcae</em>) (PSG) has been causing damage and losses to coffee growing. However, initial stages of the infectious process<em> </em>should be described in order to understand the relationship cycle and to propose efficient management strategies. This study described the initial stages of<strong> </strong>infectious process of the PSG in coffee leaves over time. The bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…As the infection process of P. syringae pv. garcae in coffee leaves has exponential increase in colonization after inoculation (Souza et al., 2019), UFV 7158 genotype possibly was more effective in the increase expression this genes of plant defence. Studies carried out with tobacco modified for PAL gene overexpression indicated that these plants were more resistant to infection by Cercospora nicotianae than wild plants (Shadle et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As the infection process of P. syringae pv. garcae in coffee leaves has exponential increase in colonization after inoculation (Souza et al., 2019), UFV 7158 genotype possibly was more effective in the increase expression this genes of plant defence. Studies carried out with tobacco modified for PAL gene overexpression indicated that these plants were more resistant to infection by Cercospora nicotianae than wild plants (Shadle et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The phytopathogenic bacterium Pseudomonas syringae pv. garcae (Psg) is responsible for the coffee halo blight disease of coffee plants [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%